Exploration of Students’ Perception of Academic Misconduct: Do Individual Factors, Moral Philosophy, Behavioral Intention, and Judgment Matter? - Huang, Chiao Ling; Yang, Shu-Ching; Yang, Chun-An (Frontiers in Psychology, 2022)
Using Reidenbach and Robin’s Multidimensional Ethics Scale, this study designs three scenarios related to academic dishonesty (AD) dilemmas to explore students’ moral philosophies, behavioral intentions and ethical judgments and further examines whether students with different individual factors (i.e., culture of place, gender, and educational level) have differences in the above variables. A total of 605 students from two areas, Taiwan and Mainland China, participated in this study. The results indicated that Taiwanese students had stricter moral equity, relativism and contractualism philosophies in the duplicate submission scenario than Mainland China students. They also had stricter moral equity and relativism philosophies in the incomplete citation scenario. Similarly, relatively harsh relativism and contractualism philosophies accompanied by a low level of willingness to be a perpetrator in the failure to cite research published in other countries scenario were found. In addition, females applied relatively harsh moral equity and utilitarianism to all scenarios, reporting that they and their peers were less likely to engage in all AD activities. Graduates had a stricter egoism attitude toward duplicate submission, and had stricter moral equity, relativism and contractualism philosophies toward the behavior of incomplete citation. Graduate students also had strict moral equity, relativism, egoism and contractualism beliefs in the failure to cite the foreign research scenario. Finally, regression analysis showed that moral equity, contractualism and self-behavioral intention are significant predictors of students’ ethical evaluations in the three scenarios.